2015
DOI: 10.1038/jid.2014.448
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prolactin-Induced Protein on Human Skin: New Insight into the Digestive Action of This Aspartic Peptidase on the Stratum Corneum and Its Induction of Keratinocyte Proliferation

Abstract: Human prolactin-induced protein (PIP) is a major protein found in exocrine fluids such as saliva and sweat. Intriguingly, PIP possesses residues (human PIP (hPIP): PIP (29-63)) that display similarity to the aspartic peptidase candidapepsin. Here, we aimed to determine the effect of PIP as a protease on normal skin structure. Using an adhesive tape-stripping technique, we applied hPIP peptide on the corneocytes of normal-appearing facial skin from infants with eczema and healthy infants and then analyzed the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Another study demonstrated that PIP is required for cell cycle progression, including the progression through G1 phase, mitosis, and cytokinesis, through regulating genes controlling these processes, such as cyclin D1, cyclin B1, BUB1, and FOXM1 [ 44 ]. Sugiura et al found that PIP could induce the proliferation of epidermal keratinocytes in a human 3-D skin model and speculated that this phenomenon might be caused by an indirect effect of PIP through stratum corneum damage [ 45 ]. Other researchers reported the opposite finding that androgens could increase the expression of PIP and strongly inhibits proliferation of breast cancer cells in an estrogen-sensitive ZR-75-1 cell line [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that PIP is required for cell cycle progression, including the progression through G1 phase, mitosis, and cytokinesis, through regulating genes controlling these processes, such as cyclin D1, cyclin B1, BUB1, and FOXM1 [ 44 ]. Sugiura et al found that PIP could induce the proliferation of epidermal keratinocytes in a human 3-D skin model and speculated that this phenomenon might be caused by an indirect effect of PIP through stratum corneum damage [ 45 ]. Other researchers reported the opposite finding that androgens could increase the expression of PIP and strongly inhibits proliferation of breast cancer cells in an estrogen-sensitive ZR-75-1 cell line [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…PIP is found in a variety of human secretions, has immunoregulatory functions, and is abundantly expressed in human cancers, especially breast cancer, where it exerts tumor-promoting actions [ 65 ]. A study showed that PIP can damage the skin barrier and induce keratinocyte proliferation [ 66 ]. Annexin A2 (ANXA2) is a member of the annexin family.…”
Section: Discussionmentioning
confidence: 99%
“…42 Prolactin-induced protein is an aspartic peptidase found in the epidermis and acrosyrinx of eccrine sweat glands. 66 Application of prolactin-induced protein to a 3D human skin model caused digestion of stratum corneum and epidermal proliferation. Dermcidin, or proteolysis-inducing factor, is a sweat ■ FIGURE 3.…”
Section: Apocrine Gland Variationmentioning
confidence: 99%